ChemInform Abstract: Discovery of 2‐Phenyl‐N‐(5‐(trifluoromethyl)‐1, 3, 4‐thiadiazol‐2‐yl)acetamide Derivatives as Apoptosis Inducers via the Caspase Pathway with Potential Anticancer Activity. Issue 16 (22nd April 2014) - Hosseinzadeh, Leila; Khorand, Amanc; Aliabadi, Alireza
Abstract 16 Title compounds of type (V) are prepared and their in vitro anticancer activities are evaluated against three cancer cell lines.